Antibacterial and antifungal activity of kenaf seed peptides and their effect on microbiological safety and physicochemical properties of some food models - Arulrajah, Brisha; Qoms, Mohammed S.; Muhialdin, Belal J.; Hasan, Hanan; Zarei, Mohammad; Meor Hussin, Anis Shobirin; Chau, De-Ming; Saari, Nazamid (Elsevier, 2022)
This study aimed to develop natural antibacterial and antifungal peptides from kenaf seed powder and to determine their efficacy in prolonging the shelf-life of fruit juices and bread systems. The kenaf seed peptides mixture (KSPM) displayed potent antimicrobial activity ranging from 94.48 to 98.99% against Gram-positive and Gram-negative bacteria and fungi. Sixteen low molecular weight cationic peptides ranging from 768 to 1416 Da were identified, in which nine of them were de novo peptides. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of KSPM against gram-positive bacteria were 11 μg/mL, 22 μg/mL for gram-negative bacteria, with a higher MIC of 43 μg/mL and minimum fungicidal concentration (MFC) of 86 μg/mL required against fungi. The KSPM displayed a rapid bactericidal effect against all the tested bacteria at 1 MIC within 1 h, and a rapid fungicidal effect against all the tested fungi at 2 MIC within 4 h. The KSPM retained a 100% of its activity up to 121 °C, 100 mM NaCl and in an acidic environment, and to a lesser extent of 64–72% under neutral condition. The peptides were fully digested by gastrointestinal proteases including pepsin, trypsin and α-chymotrypsin. The incorporation of 1000 and 3000 mg/kg KSPM in bacteria-inoculated mango and pineapple juices caused a ≥5-log10 reduction in the viable counts of Salmonella typhimurium, Escherichia coli and Listeria monocytogenes within 1–2 h during storage at 4 °C. The application of KSPM at 3000 mg/kg reduced Aspergillus niger, Aspergillus flavus and Fusarium sp. count by 3–4 log10 in fungi-inoculated bread samples when stored at 25 °C. The peptides at 1000 and 3000 mg/kg successfully extended the shelf-life of bacteria-free fruit juices for 150 days, and mould-free bread for 10 and 16 days. The addition of KSPM to fruit juices and bread model did not induce alteration to their physicochemical properties. These findings demonstrating the potential application of KSPM as a natural preservative in the food industry.